Evaluation of antagonism activity and control of vibrio alginolyticus in artemia culture using mixed probiotic - Mei, Yun Beryl Chean; Puvanasundram, Puvaneswari; Yaminudin, Jasmin; Karim, Murni (Universiti Putra Malaysia Press, 2021)
Supplementation with mixed probiotic in aquaculture has been proven to benefit the hosts as disease resistance tool. In this study, a mixed probiotic which consisted of three isolated strains (Lysinibacillus fusiformis strain SPS11, A2, and Bacillus megaterium strain I24) was formulated for the in vitro assays against Vibrio alginolyticus and in vivo preliminary study towards Artemia nauplii. These strains showed antagonism activities against V. alginolyticus in in vitro assay. An increase in biofilm formation of this mixed probiotic was observed which indicated that the strains could work synergistically with each other to confer benefits to the hosts. Enrichment of Artemia nauplii with the formulated mixed probiotic was done to investigate its role in enhancing resistance against the V. alginolyticus. Artemia nauplii were cultured in two different concentrations of mixed probiotic (106 and 108 CFU mL-1) and challenged via immersion method. The mixed probiotic at both concentrations resulted in significantly higher survival of Artemia compared to the challenged group with no probiont added (106 CFU mL-1, 65.00 ± 0.00 % and 108 CFU mL-1, 77.50 ± 3.53 %). Significant reduction of Vibrio loads was observed in Artemia and its culture water supplemented with mixed probiotic at 108 CFU mL-1 whereas there was no reduction of Vibrio at 106 CFU mL-1. This study suggests that the usage of formulated mixed probiotic at high concentration (108 CFU mL-1) as opposed to single-strain probiotic can confer protection against V. alginolyticus infection towards Artemia.